Persistence of the permeability transition pore in human mitochondria devoid of an assembled ATP synthase - Carroll, Joe (Proc Natl Acad Sci U S A, 2019)
The opening of the permeability transition pore, a nonspecific channel in inner mitochondrial membranes, is triggered by an elevated total concentration of calcium ions in the mitochondrial matrix, leading to disruption of the inner membrane and necrotic cell death. Cyclosporin A inhibits pore opening by binding to cyclophilin D, which interacts with the pore. It has been proposed that the pore is associated with the ATP synthase complex. Previously, we confirmed an earlier observation that the pore survives in cells lacking membrane subunits ATP6 and ATP8 of ATP synthase, and in other cells lacking the enzyme’s c(8) rotor ring or, separately, its peripheral stalk subunits b and oligomycin sensitive conferral protein. Here, we investigated whether the pore is associated with the remaining membrane subunits of the enzyme. Individual deletion of subunits e, f, g, and 6.8-kDa proteolipid disrupts dimerization of the complex, and deletion of DAPIT (diabetes-associated protein in insulin sensitive tissue) possibly influences oligomerization of dimers, but removal of each subunit had no effect on the pore. Also, we removed together the enzyme’s membrane bound c(8) ring and the δ-subunit from the catalytic domain. The resulting cells assemble only a subcomplex derived from the peripheral stalk and membrane-associated proteins. Despite diminished levels of respiratory complexes, these cells generate a membrane potential to support uptake of calcium into the mitochondria, leading to pore opening, and retention of its characteristic properties. It is most unlikely that the ATP synthase, dimer or monomer, or any component, provides the permeability transition pore.